Divergent Genetic Selection for Body Weight at Four Weeks Age in Japanese Quail - M. A. Fadhil (Journal of Global Pharma Technology, 2018)
Objective: The study conducted to measure the selection response of divergent genetic selection for body weight at four weeks age and its effects on other traits. Materials and methods: The experimental flock consist of 300 one day old chicks of black Japanese quail variety which divided into two groups, the first group (100 chicks) represents the control, and the second group (200 chicks) represents the base population for divergent selection. The selection procedure performed by select 30 females and 15 males for each of highest body weight (HBW) and lowest body weight (LBW) at four weeks of age, and the control line (CL) leaved without selection. The eggs of each line incubated to get the first generation, and the hatching procedure replicated three times. Results: The results showed that the average body weight at four weeks of age of unsexed birds, males and females for the base population 124.52, 129.89 and 127.21 gm. respectively. The average body weight at four weeks of age in the first generation for unsexed birds, males and females in the HBW line 147.60, 145.29 and 150.59 gm. respectively, and for LBW line 122.42, 120.26 and 125.25 gm. respectively. The selection response in the HBW group for unsexed birds, males and females 20.39, 20.77 and 20.70 gm. respectively, and for LBW line -4.80, -4.27 and -4.64 gm. respectively. There is significant difference between HBW and LBW in the body weight at six weeks of age while there is no significant difference between HBW and CL. Conclusion: There is significant improvement in HBW at six weeks can be achieved by selection for HBW at four weeks, and the natural selection assist the selection for HBW.Keywords: Japanese quail, Divergent selection, Body weight, Selection response, Realized heritability.